Bio‐Hermes: A Validation Study to Assess a Meaningful Relationship Between Blood and Digital Biomarkers with Aβ PET Scans for Alzheimer's Disease. (20th December 2022) - Beauregard, Douglas W.; Mohs, Richard; Dwyer, John; Hollingshead, Sarah; Smith, Katy; Bork, Jason; Kerwin, Diana R.
Abstract: Background: The Global Alzheimer's Platform Foundation® (GAP) has developed a biomarker study (Bio‐Hermes) that will compare results of blood and digital biomarker tests with the results of brain amyloid PET scans and traditional cognitive tests. The trial will enroll 1, 000 participants across three cohorts: Healthy, MCI, and Mild AD. In addition, Bio‐Hermes has a discrete recruiting endpoint that requires enrollment of a minimum of 200 participants (20%) from traditionally underrepresented populations (Black/African American & Latino). Bio‐Hermes will generate a unique, well‐characterized, diverse sample set that will explore the utility of several leading biomarkers. This study will contribute to reducing the time and variability of therapeutic clinical trials in Alzheimer's disease. Bio‐Hermes will generate a first of its kind, "head‐to‐head" comparison of a broad set of AD biomarkers. Method: 1. GAP activated 13 sites based on high productivity, access to a large AD population, commitment to recruiting traditionally underrepresented populations, and proof of COVID‐appropriate processes and SOPs. 2. 3 cohorts established: Cohort 1 – Healthy Cohort 2 – MCI verified Cohort 3 – Mild AD verified 3. Sites collect Aß 42/40, p‐Tau 181/217/231, NfL blood biomarkers, full gene sequencing, including APOE status, traditional cognitive tests, family history, medications, retinal scan, digital cognitive tests, and centrally read Aß PET scans. 4. Novel and focused recruitment efforts deployed to prioritize diverse representation. Result: As of 1/27/2022: 1. 6% of enrollment goal achieved (686 out of 1, 000) Cohort 1: 371 enrolled out of 400, (21% Aß Positive) Cohort 2: 244 enrolled out of 300, (34% Aß Positive) Cohort 3: 71 enrolled out of 300, (55% Aß Positive) 2. 19% from traditionally underrepresented populations 3. Screen fail rate of 15.9% 4. 208 participants enrolled in the Retispec Sub‐Study Conclusion: Bio‐Hermes provides a well‐characterized, highly useful dataset including one of the most diversified populations in an AD study, illustrating that traditionally underrepresented populations can be successfully recruited. This study facilitates the discovery of potential biomarkers when compared to Aß PET and validates their predictive value for assessment/screening purposes. Bio‐Hermes is establishing a subset of potential participants for downstream AD therapeutic trials that will significantly lower screen fail rates.